Participation-Based Student Goals in School-Based Physical Therapy Practice: Influence on Service Delivery and Outcomes. (3rd September 2021) - Wynarczuk, Kimberly D.; Chiarello, Lisa A.; Gracely, Edward; Effgen, Susan K.; Palisano, Robert J.; Fisher, Kathleen
Abstract: Aims: Legislation, perspectives, and guidelines support the use of goals that address student participation in school. The purpose of this study was to determine if students with participation-based goals receive school-based physical therapy services differently and demonstrate better outcomes than students with non-participation-based goals. Methods: Secondary data analysis. School-based physical therapists ( n  = 109) provided services to students ( n  = 294) over 20 weeks. The physical therapists determined a primary goal for each student and classified this goal based on if it was ( n  = 181) or was not ( n  = 113) performed and measured within a school activity or routine (participation-based versus non-participation-based). The physical therapists documented the proportion of services provided within a school activity, on behalf of the student, and consisting of activity-focused functional activities. They also measured goal attainment and assessed participation via the School Function Assessment at the beginning and end of the study. Results: Students with participation-based goals received a significantly greater proportion of services within a school activity than those with non-participation-based goals ( p  < 0.001). There was no significant difference for the remaining service variables, nor for the outcome variables. Conclusions: Use of participation-based goals may promote school-based physical therapy service delivery within a school activity, thus supporting best practice.